Post salpingectomy intraluminal endometriosis in a premenopausal lady - an incidental finding often paid less attention to - Sandhyarani, Kanna; Shetty, Archana; Nagabhushan, Bhargavi Kalburgi; Muralidhar, Aparna; Minal, Jessica; Moorchung, Nikhil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometriosis of the fallopian tube is often incidentally picked up in hysterectomy specimens that are sent for histopathological examination for other obvious pathological conditions. Post-salpingectomy endometriosis is one such entity that is known to occur in the tip of the proximal stump of the fallopian tube years after tubal ligation. As mere visualization of the endometriotic lesions is inadequate for an accurate diagnosis, histopathologic analysis of the biopsy samples becomes mandatory for confirmation. We report a case of post salpingectomy endometriosis which was incidentally discovered in a peri menopausal lady who was operated for multiple fibroids of the uterus. This case not only highlights an entity which is challenging to visualize radiologically and suspect clinically, but is also underrecognized, as very little attention is given to the fallopian tube during routine grossing.